Empowering Executive Functions in 5- and 6-Year-Old Typically Developing Children Through Educational Robotics: An RCT Study - Di Lieto, Maria Chiara; Pecini, Chiara; Castro, Emanuela; Inguaggiato, Emanuela; Cecchi, Francesca; Dario, Paolo; Cioni, Giovanni; Sgandurra, Giuseppina (Frontiers in Psychology, 2020)
Educational Robotics (ER) is a new learning approach, known mainly for its effects on scientific academic subjects such as science, technology, engineering and mathematics. Recent studies indicate that ER can also affect cognitive development by improving critical reasoning and planning skills. This study aimed to quantify the ability of ER to empower Executive Functions (EF), including the ability to control, update, and program information, in 5- and 6-year-old children attending first grade, a crucial evolutionary window for development of such abilities. A total of 187 typically developing children were enrolled and randomly allocated into two experimental conditions: A, for immediate ER training, and B, for waitlist. ER-Laboratories for small groups were organized at schools, using a child-friendly, bee-shaped robot called Bee-Bot® (Campus Store). Activities were intensive, enjoyable, and progressively more challenging over the 20 twice-weekly sessions. Outcome measures, based on standardized tests, were used to quantify ER effects on EF. Compared to the control group, the ER-Lab group showed significantly better ability to actively manipulate information in short-term memory and suppress automatic responses in favor of goal appropriate actions. This RCT study provides the first quantitative evidence of the positive effects of ER activities for improving working memory and inhibition in the early school years.